88. Integration of MR-tractography into radiation treatment planning for high-grade glioma. (December 2018) - Altabella, L.; Broggi, S.; Mangili, P.; Conte, G.M; Iadanza, A.; del Vecchio, A.; Anzalone, N.; Di Muzio, N.; Caladrino, R.; Falini, A.; Castellano, A.
Abstract : Purpose: Radiotherapy in brain tumors is associated with several detrimental effects. White-matter (WM) regions are associated with higher radiosensitivity respect to grey-matter but no dose constraints are used[1] . Magnetic Resonance(MR)-Tractography is the only technique that allows to in-vivo visualize WM eloquent tracts adjacent/inside brain tumors[2] . In this work feasibility of MR-Tractography integration in treatment planning is investigated aiming to spare eloquent regions from dose delivered during RT-treatment. Methods: 19 patients with high-grade-gliomas underwent MR acquisitions before RT (1.5 T scanner), including structural images and DTI sequence (32 or 15 directions, b-value = 1000 s/mm 2 ) and structural imaging for Target and OAR definition. RT-treatment was delivered with helical tomotherapy. Bilateral tracts considered are: corticospinal tracts (CST), superior-longitudinal fascicle (SLF), inferior fronto-occipital fascicle (IFOF) and uncinate fascicle (UNC). Tracts were then converted in binary masks and then imported in TPS for automatic contouring. The original plans were compared with optimized plans including WM-tracts. Results: No significant differences were found for PTV coverage between plans (p = 0.29). Comparing mean-dose and Dmax significant dose reduction for all tracts was found (results for mean-dose are reported in table for contralateral and omolateral-tracts). DVH analyses showed that low doses are reduced for contralateral-tracts and V30 for all tracts except for CST (p = 0.28). For omolateral-tracts significantly reduction was achieved for SLF and IFOF (p < 0.05). Conclusions: Integration of MR-Tractography into RT-planning is feasible and beneficial to spare important WM structures without reducing clinical goal of RT-treatment.